2016
DOI: 10.1016/j.drudis.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Computational functional group mapping for drug discovery

Abstract: Computational functional group mapping (cFGM) is emerging as a high-impact complement to existing widely used experimental and computational structure-based drug discovery methods. cFGM provides comprehensive atomic-resolution 3D maps of the affinity of functional groups that can constitute drug-like molecules for a given target, typically a protein. These 3D maps can be intuitively and interactively visualized by medicinal chemists to rapidly design synthetically accessible ligands. Given that the maps can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
10
0
4
Order By: Relevance
“…Another useful in silico method, particularly beneficial for lead optimization, is quantitative structure‐property relationship (QSPR) modeling which is useful for the identification of key structural features responsible for interacting with the target protein. For many ADME endpoints measured in the pharmaceutical industry, QSPR models have prospectively shown their ability to extract knowledge from a wide variety of chemical scaffolds proving their utility as predictive models . QSPR models, based on machine learning techniques, are desirable to achieve the optimal potency and ADME properties.…”
Section: Introductionmentioning
confidence: 99%
“…Another useful in silico method, particularly beneficial for lead optimization, is quantitative structure‐property relationship (QSPR) modeling which is useful for the identification of key structural features responsible for interacting with the target protein. For many ADME endpoints measured in the pharmaceutical industry, QSPR models have prospectively shown their ability to extract knowledge from a wide variety of chemical scaffolds proving their utility as predictive models . QSPR models, based on machine learning techniques, are desirable to achieve the optimal potency and ADME properties.…”
Section: Introductionmentioning
confidence: 99%
“…Es posible implementar el diseño estructural computacional de compuestos como herramienta para determinar dicho equilibrio de interacción [23,29]. Esta herramienta predice la energía libre de unión a partir de la flexibilidad estructural entre el compuesto candidato y su diana cuando se da una interacción entre ambos.…”
Section: La Estructura Molecular Y Su Importancia En El Descubrimientunclassified
“…Dentro de las consideraciones estructurales se encuentra que el tamaño molecular puede determinar el grado de interacción entre el candidato y el blanco [31]. Compuestos pequeños, con peso molecular <500 Da o menos de 20 átomos sin contar átomos de hidrógeno [32], presentan enlaces C-H que aportan significativamente a la energía libre de unión [30]; siempre y cuando estos enlaces pertenezcan a los grupos funcionales más próximos a la superficie del blanco terapéutico [29]; por lo tanto, a mayor energía libre de unión, mayor afinidad de unión entre candidato-blanco.…”
Section: La Estructura Molecular Y Su Importancia En El Descubrimientunclassified
See 1 more Smart Citation
“…Despite the functional and structural diversity of different protein-binding ligands, many of them share same or similar functional groups (FGs) that mediate the interactions with the target proteins. Therefore, identification of conserved 3D binding motifs for FGs shared by different small molecules may extend our understanding of protein-ligand interactions to higher resolution and broader scope (Guvench, 2016). Previous studies have shown that conserved 3D motifs do exist in proteins binding different ligands with the same FG.…”
Section: Introductionmentioning
confidence: 99%